THE SYNTHESES OF [BzMe3N]2[Mo4O10(OMe)6] - Bakri, Ridla (Makara Journal of Science, 2002)
In an attempt to synthesize [BzMe3N]2Mo2O5(OMe)5 from the reaction of [BzMe3N]2MoO4 and MoO(OMe)4 in the ratio of 1:1 in methanol has produced [BzMe3N]2Mo4O10(OMe)6. The formation of [Mo4O10(OMe)6]2- anion suggests that ligand dissociation has occured in solution. Suitable crystals for X-ray chrystallographic were obtained from hot methanol and the crystal structure of [BzMe3N]2Mo4O10(OMe)6 has been solved and reported here in.